Stability and Liftoff of a N2-in-H2 Jet Flame in a Vitiated Co-flow at Atmospheric Pressure - A. A. North (Eurasian Chemico-Technological Journal, 2014)
The stability and liftoff characteristics of a nitrogen (N2) diluted hydrogen (H2) jet flame in a vitiated co-flow are investigated experimentally with particular attention focused on regimes where multiple stabilization mechanisms are active. Information gleaned from this research is instrumental for informing modeling approaches in flame transition situations when both autoignition and flame propagation influence combustion characteristics. Stability regime diagrams which outline the conditions under which the flame is attached, lifted, blown-out, and unsteady are experimentally developed and explored. The lifted regime is further characterized in determining liftoff height dependence on N2 dilution, jet velocity, and co-flow equivalence ratio (or essentially, co-flow temperature). A strong sensitivity of liftoff height to N2 dilution, jet velocity, and co-flow equivalence ratio is observed. Liftoff heights predicted by Kalghatgi’s correlation are unable to capture the effects of N2 dilution on liftoff height for the heated co-flow cases. A uniquely formulated Damköhler number, where the chemical time scale is based on flame propagation rather than autoignition, was therefore developed which acceptably captures the effects of jet velocity, nitrogen dilution and environment temperature on liftoff height. Satisfactory agreement between the correlation results indicate that stabilization is dominated by propagation, and prior studies with similar flames, such as the research of Muñiz and Mungal (1997) indicate that the propagating flame is likely tribrachial.